The Influence of Company Size, Profitability, Solvency, Current Ratio, and Capital Structure on Going Concern Audit Opinions in Consumer Sector Companies Listed on the Indonesia Stock Exchange (BEI) 2019-2022 - Lusia Efrina Juniawan Siahaan; Jagar Tua Sihombing; Siti Aisyah Nasution; Wenny Anggeresia Ginting (Cita konsultindo, 2024)
The rapid expansion of the global economy has led to a proliferation of entities or corporations, resulting in intensified economic competition in the commercial realm. Entrepreneurs devise and execute plans pertaining to the acquisition and divestment of corporate assets, including those associated with Indonesian Stock Exchange establishments, in order to assure the ongoing viability of their economic endeavors. As the quantity of entities or firms grows, there is a corresponding rise in the need for auditing financial reports. Annually, organizations or corporations strive to generate a financial gain while ensuring the ongoing operation of their firm. An entity's financial reports are founded on the essential assumption of business continuity, sometimes referred to as going concern, which establishes its degree of viability. This assumption enables the company's operations to sustain business in the long term. In order to ensure the uninterrupted operation of their firm, several organizations opt to secure loans from banks or undergo the process of becoming publicly traded businesses to acquire more capital from investors. To persuade investors, the business must have confirmation from external sources regarding the company's management performance and financial situation. In order to instill trust in the financial reports of the organization, an external auditing firm (KAP) carries out audits. Auditors have a vital responsibility in verifying that financial reports are devoid of any fraudulent activities or misrepresentation. This allows users and investors to make well-informed and accurate judgments. This study utilizes a quantitative methodology, categorizing the data as either quantitative or in numerical form. The secondary data for this research was acquired from the annual financial reports of consumption sector businesses listed on the IDX for the period of 2019–2022, accessed through the official website of the Indonesia Stock Exchange (BEI). The findings of this study indicate that the profitability variable has a simultaneous impact on the going concern audit opinion in logistic regression testing. However, the going concern audit judgment is not influenced by factors such as firm size, solvency, current ratio, and capital structure.